Development of a Camel Kidney Cell Strain and Its Use in Virology - Mirchamsy, H. (1970)
A strain of camel kidney cells was developed and carried in serial passages. The subcultures were slow-growing in the early passages and were composed of heterogeneous cell population. By the 35th passage, the growth rate increased, and more homogeneous cells, mostly of the epithelioid type, were seen. The cell strain was highly susceptible to West Nile, Sindbis, vesicular stomatitis, adeno, and vaccinia viruses, and also was susceptible to herpes simplex, rinderpest, measles, and canine distemper viruses.